CMDB systems making change work in the age of Cloud and Agile - Drogseth, Dennis; Sturm, Rick; Twing, Dan (Morgan Kaufmann, 2015)
CMDB Systems: Making Change Work in the Age of Cloud and Agile shows you how an integrated database across all areas of an organization's information system can help make organizations more efficient reduce challenges during change management and reduce total cost of ownership (TCO). In addition, this valuable reference provides guidelines that will enable you to avoid the pitfalls that cause CMDB projects to fail and actually shorten the time required to achieve an implementation of a CMDB.